Response of lentil to bio and chemical fertilizers at farmers field (Bangladesh Journal of Agricultural Research, 2015)
Field trials were carried out at the Farming System Research & Development site, Hatgavindapur, Faridpur, On-Farm Research Division of Bangladesh Agricultural Research Institute during rabi seasons of 2006-2007 and 2007-2008 with the objectives to evaluate the response of lentil to Rhizobium biofertilizer and to reduce the use of N-fertilizer under farmers field condition. The experiment was laid out in Randomized Complete Block Design (RCBD) with four replications. Unit plot size was 4 m x 5 m. Four fertilizer treatments viz. T1: 24-22-42-20-5 kg N-P-K-S-Zn ha-1, T2: 50-22-42-20-5 kg N-P-K-S-Zn ha-1, T3: 0-22-42-20-5 kg N- P-K-S-Zn ha-1 + Rhizobium Inoculum and T4: Farmers practices were studied. Farmers practice was 25-18-21-0-0 kg N-P-K-S-Zn ha-1. BARI Masur-4 and peat based rhizobial inoculum (strain BARI RLc-102) @ 1.5 kg ha-1 were used. Result revealed that application of Rhizobium biofertilizer along with PKSZn chemical fertilizers produced the highest nodule number (11.62 plant-1) and nodule weight (11.94 mg plant-1), and the seed yield 1.44 t ha-1. The seed yield was higher in T3 treatments (N0P22K42S20Zn5 + Inoculum) than T1 (N24P22K42S20Zn5) and T2 (N50P22K42S20Zn5) treatments. No variation was observed in seed yield in treatments T1, T2 and T3 but significantly different from farmers practice. Farmers practice showed the lowest yield. Economic analysis revealed that T3 treatment i.e. PKSZn plus Rhizobium inoculum gave the highest 5.36 benefit cost ratio (BCR) followed by T1 4.68 and T2 3.61. It is evident from the experiment that application of biofertilizer can be used as substitute of nitrogenous fertilizer for higher yield of lentil at farmers field in Faridpur.Bangladesh J. Agril. Res. 40(3): 501-506, September 2015